Early postoperative magnetic resonance imaging after resection of malignant glioma: objective evaluation of residual tumor and its influence on regrowth and prognosis - Albert, Friedrich; Forsting, Michael; Sartor, Klaus; Adams, Hans-Peter; Kunze, Stefan (Neurosurgery, 1994)
IN THE VAST majority of studies that address the role of surgery in the management of high-grade gliomas, the degree of tumor removal accomplished is solely based on the intraoperative perception of the neurosurgeon. Despite its fundamental importance for a comparison of different treatment modalities, little systematic effort has been made to evaluate the residual gross tumor by neuroimaging methods immediately after surgery. We report the results of a prospective study using contrast-enhanced computed tomography and magnetic resonance imaging (MRI) to monitor 60 patients after the resection of a high-grade glioma. In each case, the first scans were obtained between Days 1 and 5 after surgery, followed by serial imaging every 2 to 3 months, usually until the condition of the patient deteriorated severely or the patient died. Gadolinium-enhanced MRI proved to be extremely valuable for assessing gross residual tumor when performed during Days 1 to 3 after the resection of a preoperatively enhancing high-grade glioma. This timing avoided surgically induced contrast enhancement and minimized interpretative difficulties. In delineating residual tumor, MRI was vastly superior to computed tomography. About 80% of tumor “recurrences” emerged from definitely enhancing remnants, as revealed by early postoperative MRI. The neurosurgeon's estimation of gross tumor burden reduction could be shown to be much less accurate (by a factor of 3) than the postoperative assessment by modern neuroimaging. In our series, residual tumor enhancement was the most predictive prognostic factor of survival in patients with glioblastoma, followed by radiotherapy. Patients with a residual tumor postoperatively had a 6.595-times higher risk of death in comparison to patients without a residual tumor. Patients undergoing radiotherapy had a 0.258-times lower risk of death in comparison to patients who were not treated with radiation. Concerning survival, the prognostic significance of both variables surpassed age and performance.
Gesehen am 23.08.2023